Semantic modelling of road traffic information elements - Samper Zapater, José Javier; Carrillo Zambrano, Eduardo; Cervera García, Arturo (Revista Colombiana de Computación, 2006)
Nowadays there are vocabularies or languages that describe concepts and structures of data related to traffic, but the description is just syntactic, not semantic. No vocabularies or ontologies with semantic value that give significance to concepts and their relations were found (at least up to where the search and bibliographic revision of this work took us) which we could have taken as a starting point for our research so this emptiness was covered by its own construction. Keywords: Semantic Web, Ontologies, Road Trafffic Information , Semantic language, Multilingual